L’intégration du secteur privé dans l’exploitation écotouristique des parcs nationaux colombiens. L’exemple du Parc amazonien Amacayacu - Mara Sierra Jiménez; Jean-Yves Puyo (Études Caribéennes)
The market of ecotourism services comes to light as one of the main challenges of management in certain protected territories today. The Amazonian park Amacayacu, in Colombian Amazonia, belongs to one of these territories where the need of improvement of the infrastructures of management and the ecotourism services becomes indispensable to guarantee the continuity of management of this protected territory and the economic survival of the local human groups. For that purpose, since 2005, the device set up by the Colombian government consisted in giving in concession the management of the ecotourism services of this park to the private sector. First of all, this research tries to identify, at every level (local, regional, national), the stages and the devices set up in this process of concession. Secondly, it will be a question of bringing to light the impacts of this new model of territorial joint management on the natural and cultural heritages as well as on the Amerindian populations which live in the territory. Finally, we shall question the efficiency of the device of concession of the management of the park Amacayacu and its zones of confluence, by attaching us more particularly to the study of the community Ticuna de Mocagua.